Interventionist research in accounting : a methodological approach - Baard, Vicki; Dumay, Johannes (New York, NY : Routledge, 2021)
"This book is the first comprehensive methodological guide for accounting researchers on Interventionist Research (IVR). It provides all the fundamental components needed for understanding what IVR is, and how to plan, design, and conduct legitimate intervention studies, which can endure the scrutiny of institutions and peer review. This text systematically opens the 'black box' of an alternative research paradigm seeking to contribute simultaneously to theory and practice, through direct and collaborative engagement with organisations, practitioners, managers and professionals. It mobilises the production of innovative and theoretically grounded research for academe, and of practical relevance or usefulness and interest to the field of practice"--
OCLC-licensed vendor bibliographic record.
Keywords: Accounting -- Research; Intervention (Administrative procedure); BUSINESS & ECONOMICS / Accounting / General; BUSINESS & ECONOMICS / Accounting / Financial; BUSINESS & ECONOMICS / Accounting / Managerial